Hubungan Panjang Tungkai, Power Tungkai Dan Kekuatan Otot Tungkai Dengan Akurasi Shooting Ekstrakurikuler Futsal - Alfath Nurfadlillah; Arifai Arifai (Universitas Hamzanwadi, 2026)
Shooting accuracy in futsal is an important skill that is influenced by various physical factors, but studies that simultaneously integrate leg length, leg power, and leg muscle strength are still limited. This study aims to determine the relationship between leg length, leg power, and leg muscle strength with shooting accuracy among students participating in the extracurricular futsal program at SMA N 14 Bandar Lampung. The research method used a quantitative approach with a cross-sectional correlational design. The research population consisted of all students participating in the futsal extracurricular activity, numbering 25 people, and all of them were used as samples (total sampling). The instruments used included an anthropometer, vertical jump test, leg and back dynamometer, and a ball shooting test at a target. Data analysis used Pearson Product Moment correlation and multiple correlation. The results showed a significant relationship between leg length and shooting accuracy (r = 0.764), leg power and shooting accuracy (r = 0.742), leg muscle strength and shooting accuracy (r = 0.786), and all three variables simultaneously with shooting accuracy (R = 0.873; R² = 0.762; p < 0.05). The conclusion of this study is that leg length, leg power, and leg muscle strength, both individually and collectively, have a positive and significant relationship with shooting accuracy, with a contribution of 76.2%.